Implikasi Bias Jender terhadap Manajemen Sumber Daya Manusia di Lembaga Pendidikan Dasar Bercirikan Agama - Nurul Ulfatin (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2000)
Implications of Gender Bias for Human Resource Development Management in Education Institution Characterized by Religion. The study aimed at describing gender bias and exploring its implications for human resource development management in education institution having religious characteristics. This qualitative case study involved Sunan Kalijaga Islamic Elementary School at Malang. The data were collected through in-depth interview, observation, and documentation study. The results of qualitative analyses indicate that in such education institution exists gender bias, which is reflected not in physical conditions but in human life within the institution. Gender bias is reflected in the implementation of outside-classroom activities, which might influence the teaching-learning process, and has effect on management, mainly management of human resource development and leadership.